Analisis Pembelian Tidak Terencana pada Toko Online Shopee - Wulan, Winda Noor Nawang; Suharyati, Suharyati; Rosali, Rosali (Fakultas Ekonomi dan Bisnis, Universitas Pembangunan Nasional Veteran Jakarta, 2019)
The development of information and communication technology in the era of globalization is growing rapidly. This has a significant impact on internet usage in Indonesia. So that makes Indonesia a very potential market for e-commerce, which has triggered the emergence of various online stores in Indonesia. Achieving success in e-commerce business in online stores in Indonesia requires a strategy. Shopee is an e-commerce company that runs the C2C mobile marketplace business, which allows users to buy or sell goods through applications available on the iOS and Android platforms. This research is a quantitative research that aims to determine the effect of functional comfort and representative excitement on Impulse Buying. Data collection uses a questionnaire with a Likert scale with PLS (Partial Least Square) method with Smart PLS 3.2.7 software. The sample used in the study was 50 people. The sampling technique uses a purposive sampling method. The results of this study indicate that functional convenience variables have a significant effect on unplanned purchases, while representative excitement variables have no significant effect on Impulse Buying.